Role of world financial insitutions in de-shadowing of global economy - Оlena Baula; Olena Liutak (Економічний форум)
The article examines the practical aspects of the influence of world financial institutions on preventing the spread of shadowing processes in the global economy. The systematization of literary sources and approaches to the solution of the investigated problem shows that despite the diversity and content of views surrounding the problems of detinization of the global and national economy, the development of aspects of the possible role of global financial institutions in these processes remains at an insignificant level. The methodological basis of the research is the methods of economic analysis and fundamental research: system analysis, synthesis and comparative analysis to outline the main directions and means of detinization of the economy; a functional-systemic approach for assessing the state and trends of the shadow sector of the global economy and determining its impact on the country's international competitiveness; generalization method for forming research conclusions. The object of the study is the process of detinization of the global economy with the help of the potential of world financial organizations. The article assesses the level of economic shadowing, tolerance to corruption, and the level of international competitiveness of Ukraine and its close neighbors - the countries of the Visegrad Group (Poland, the Czech Republic, Hungary and Slovakia), the USA - the world's first economy, Denmark and Switzerland - the leading countries in the rating international competitiveness. The article empirically confirms that the strategic directions of detinization of the global economy require coordinated and comprehensive actions of international organizations. The elements of the complex of detinization of the economy on a global scale are characterized, which can be effectively implemented and observed only if international institutions, in particular, financial institutions, intervene in these processes. The directions of influence of international financial institutions regarding the detinization of the global economy are determined. The conducted research proves the need for multi-vector cooperation with international financial organizations and highly developed countries that have in their arsenal effective mechanisms of detinization of economic activity. The results of the study can be useful for the development of science-based recommendations for improving the mechanisms of cooperation with international financial institutions for the effective detinization of the global economy